FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KORUPSI PEMERINTAH DAERAH DI INDONESIA - Muhammad Syauqi Qur'ani Putra Ariva (2020)
This research is motivated by the high level of corruption that occurs in Indonesia which is signalled by the low Corruption Perception Index (CPI) score in 2019. The majority of corruption cases in Indonesia involved local governments. The high level of local government corruption is related to government size, fiscal decentralization, and audit findings. The purpose of this research is to examine the factors that cause high levels of corruption in local governments. This study used a purposive sampling method and obtained a sample consisted of 90 district governments and 18 municipal governments in Indonesia in 2018. Data were analyzed using a classic assumption and hypothesis testing technique, multiple linear regression using Statistical Package for the Social Sciences (SPSS). The results of this study indicate that the variables of government size, fiscal decentralization, and audit findings have a significant influence on the level of corruption. Fiscal decentralization and audit findings have a negative effect on the level of corruption, while government size variables have a positive effect on the level of corruption. This research contributes to auditing practices, government administration, law enforcement, and corruption control initiatives in the local government of Indonesia.